Is xenodontine snake reproduction shaped by ancestry, more than by ecology? - Bellini, Gisela Paola (2017)
One of the current challenges of evolutionary ecology is to understand the effects of phylogenetic history (PH) and/or ecological factors (EF) on the life-history traits of the species. Here, the effects of environment and phylogeny are tested for the first time on the reproductive biology of South American xenodontine snakes. We studied 60% of the tribes of this endemic and most representative clade in a temperate region of South America. A comparative method (canonical phylogenetic ordination—CPO) was used to find the relative contributions of EF and PH upon life-history aspects of snakes, comparing the reproductive mode, mean fecundity, reproductive potential, and frequency of nearly 1,000 specimens. CPO analysis showed that PH or ancestry explained most of the variation in reproduction, whereas EF explained little of this variation. The reproductive traits under study are suggested to have a strong phylogenetic signal in this clade, the ancestry playing a big role in reproduction. The EF also influenced the reproduction of South American xenodontines, although to a lesser extent. Our finding provides new evidence of how the evolutionary history is embodied in the traits of living species.